2017
DOI: 10.1002/admi.201700738
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ferromagnetic Cobalt‐Doped ZnO Structures Formed by Deep‐UV Direct‐Patterning

Abstract: COMMUNICATION (1 of 8)structures patterned by holographic dissolution technique. [1] Photopatterned metal oxide structures have shown excellent electrical, optical, and magnetic properties. [2][3][4][5][6] Compared to conventional lithography techniques, photopatterning technologies significantly simplify the process, avoiding in particular the etching step that is delicate on metal oxide and requires toxic chemicals and sophisticated setup. The feature line-width of photo patterned metal oxide structures is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Additionally, no significant residual carbon contamination from incomplete precursor decomposition was detected within the film, which is known to deteriorate TFT performance severely. [11b] Only trace carbon signals were found on the surface arising from adsorbed environmental species like CO 2 . Furthermore, such treated IZO and ZTO films still exhibit a low surface roughness, i.e., R RMS ≈0.23 nm for IZO and R RMS ≈0.25 nm for ZTO after all processing steps, i.e., UV treatment, washing, and further annealing at 350 °C ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, no significant residual carbon contamination from incomplete precursor decomposition was detected within the film, which is known to deteriorate TFT performance severely. [11b] Only trace carbon signals were found on the surface arising from adsorbed environmental species like CO 2 . Furthermore, such treated IZO and ZTO films still exhibit a low surface roughness, i.e., R RMS ≈0.23 nm for IZO and R RMS ≈0.25 nm for ZTO after all processing steps, i.e., UV treatment, washing, and further annealing at 350 °C ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A higher thermal budget was needed in this case owing to a higher annealing temperature to ensure suitable decomposition of the bulky methacrylate ligand, which provides scope for improved design for metal oxide precursor for a facile photopatterning approach. [11b] Although photopatterning approaches using indium‐based precursors have been demonstrated so far, indium‐free alternative such as ZTO to generate photopatterned amorphous oxide TFTs has not yet been reported to the best of our knowledge. Such a direct photoactive precursor‐solvent system would be ideal to advance the progress in this direction to enable photopatterning of various functional metal oxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…f) DUV‐induced crosslinking improves the uniformity of Co ions in ZnO lattice. d–f) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Solution Direct‐patterned Mo Micro‐ and Nanostructures For Smentioning
confidence: 99%
“…Moreover, by using SDP techniques, TM‐doped MO nanostructures can be easily obtained. Yeh et al demonstrated ferromagnetic Co‐doped ZnO nanostructures by using a Co‐doped ZnMAA precursor that can be crosslinked by DUV irradiation, as shown in Figure d . By using DUV‐interference patterning, periodic Co‐doped ZnO lines with a 300 nm line width can be fabricated (Figure e).…”
Section: Solution Direct‐patterned Mo Micro‐ and Nanostructures For Smentioning
confidence: 99%